Effects of age, sex, race/ethnicity, and allergy status in obesity‐related pediatric asthma. Issue 11 (30th August 2019) - Lang, Jason E.; Bunnell, H. Timothy; Lima, John J.; Hossain, Md Jobayer; Wysocki, Tim; Bacharier, Leonard; Dempsey, Amanda; Ulrich, Lisa; Test, Matthew R.; Forrest, Christopher B.
Abstract: Rationale: Obesity in children increases the risk for new asthma. How age, sex, race/ethnicity, and allergy status affect the relationship between obesity and asthma is unclear. This study describes the relationship between high body mass index (BMI) and incident asthma. Methods: We conducted a retrospective cohort study to compare asthma incidence among normal weight, overweight, and obese 2 to 6, 7 to 11, and 12 to 17 year olds to define the effects of sex, race/ethnicity, and allergy status. Weight status was determined at baseline and asthma incidence was defined as ≥2 asthma encounters and ≥1 asthma prescriptions. We used multivariable Poisson regression to estimate adjusted incident asthma rates and risk ratios. Results: Data from 192 843 2 to 6 year olds, 157 284 7 to 11 year olds, and 157 369 12 to 17 year olds were included. The relative risks (95% confidence interval [CI]) of new asthma among obese children in 2 to 6 year olds, 7 to 11 year olds, and 12 to 17 year olds were 1.25 (1.15, 1.37), 1.49 (1.32, 1.69) and 1.40 (1.21, 1.63), respectively. Among children with underlying allergic rhinitis, obesity did not increase the risk of new asthma. In children without allergic rhinitis, the risk for obesity‐related asthma was highest in 7 to 11 year olds (risk ratio = 1.50 95% CI, 1.33, 1.60). Before age 12, females had a higher risk for obesity‐related asthma; but after age 12, obese males had a higher asthma risk (interaction P ‐value < .05). Conclusion: Obesity is a major preventable risk factor for pediatric asthma that appears to vary along the pediatric age continuum and depends on sex, race/ethnicity and atopy status.